2013
DOI: 10.1128/genomea.00184-12
|View full text |Cite
|
Sign up to set email alerts
|

Genome of a Gut Strain of Bacillus subtilis

Abstract: Bacillus subtilis is a Gram-positive, rod-shaped, spore-forming bacterium. We present the genome sequence of an undomesticated strain, BSP1, isolated from poultry. The sequence of the BSP1 genome supports the view that B. subtilis has a biphasic lifestyle, cycling between the soil and the animal gastrointestinal tract, and it provides molecular-level insight into the adaptation of B. subtilis to life under laboratory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…We also showed that Spo0A was more active in BSP1 cells. M-CGH studies as well as PCR suggested that the operons coding for the RapE, RapI, and RapK phosphatases are absent from BSP1, and the recent sequencing of the BSP1 genome confirms this inference (59). The absence of RapE, RapI, and RapK appears to be the primary cause of the increased sporulation of BSP1, because reintroduction of combinations of the missing rap-phr operons into BSP1 lowers the levels of Spo0AϳP, the fraction of cells expressing high-threshold Spo0A-dependent genes, and the titer of spores during the initial hours of the stationary phase in DSM.…”
Section: Discussionmentioning
confidence: 49%
“…We also showed that Spo0A was more active in BSP1 cells. M-CGH studies as well as PCR suggested that the operons coding for the RapE, RapI, and RapK phosphatases are absent from BSP1, and the recent sequencing of the BSP1 genome confirms this inference (59). The absence of RapE, RapI, and RapK appears to be the primary cause of the increased sporulation of BSP1, because reintroduction of combinations of the missing rap-phr operons into BSP1 lowers the levels of Spo0AϳP, the fraction of cells expressing high-threshold Spo0A-dependent genes, and the titer of spores during the initial hours of the stationary phase in DSM.…”
Section: Discussionmentioning
confidence: 49%
“…Bacillus subtilis can survive and reproduce in the murine gut (Hoa et al ., ; Tam et al ., ), and in the case of PXN21, this strain has been shown to persist in the GI tract of mice for 18 days following a single oral dose of spores (Permpoonpattana et al ., ). Although often considered a soil‐based organism, it is likely that B. subtilis has adapted for at least transient colonisation of the animal GI tract (Hong et al ., ; Schyns et al ., ). Reduced success of predosing could therefore be due to individual variation in animals in terms of successful colonisation.…”
Section: Discussionmentioning
confidence: 97%
“…plantarum (UCMB5033) has been published (Niazi et al., ). The whole genome of an isolate from the gut of an organically reared broiler reported as B. subtilis has been published (Schyns et al., ). The whole genome sequences of 20 isolates reported to belong to B. anthracis , B. atrophaeus , B. cereus , B. licheniformis , B. macerans , B. megaterium , B. mycoides and B. subtilis have been published (Daligault et al., ).…”
Section: Assessmentmentioning
confidence: 99%